Seeking rights from the left : gender, sexuality, and the Latin American pink tide - Friedman, Elisabeth J., 1966- (Duke University Press, 2019)
The contributors to Seeking Rights from the Left evaluate the impact of the Latin American "Pink Tide" of left-leaning governments (2000-2015) on feminist, women's, and LGBT movements and issues.